The Prevalence of Adjacent Segment Disease and Reoperation Following Transpedicular Screw Fixation of Lumbar Spine - Shallaw Mahdi Saleem; Hoshanc Sdeeq Rashid; Anjam Ibrahim Rowandizy (Zanco Journal of Pure and Applied Sciences, 2023)
Background: Adjacent segment disease is a condition in which the mobile level next to the fused section degenerates as a result of increased biomechanical stress and mobility, it may be rostral, caudal, or both rostral and caudal to fused segment. Patients and Methods: A retrospective study was conducted on 110 patients who underwent transpedicular screw fixation of the lumbar spine between January 2011 and May 2019. Demographic data of the patients, including patient’s age, gender, symptoms, type of fixation, the extent of fixation, segments fixed, date and pathology causing first and second surgery, were taken from patients attending the outpatient department of Hawler Teaching Hospital on Mondays and Wednesdays from October 2018 to May 2021. Results: Thirty-six (32.72%) patients of 110 patients who were included in the study developed ASD. Eleven (10%) patients needed a second surgery for ASD. Conclusions: The rate of developing ASD was (32.72%) out of 110 patients who were included in our study and had transpedicular screw fixation. The rate of patients that needed a second surgery for ASD was (10%). Male gender, advanced age, floating fixation and multiple level fixation were variables that contributed to a higher rate of developing ASD. Multiple level fixation was the only variable with clinical significance. These rates in our study were comparable with the literature's stated prevalence of ASD after spinal fixation and reoperation for ASD.